Nitration of particle-associated PAHs and their derivatives (nitro-, oxy-, and hydroxy-PAHs) with NO₃ radicals - Zhang, Yang; Yang, Bo; Gan, Jie; Liu, Changgeng; Shu, Xi; Shu, Jinian (Atmospheric environment (1994), 2011)
The heterogeneous reactions of typical polycyclic aromatic hydrocarbons (PAHs) and their derivatives (nitro-, oxy-, and hydroxy-PAHs) adsorbed on azelaic acid particles with NO₃ radicals are investigated using a flow-tube reactor coupled to a vacuum ultraviolet photoionization aerosol time-of-flight mass spectrometer (VUV-ATOFMS). The mono-nitro-, di-nitro-, and poly-nitro-products from successive nitro-substitution reactions of PAHs and their derivatives are observed in real time with VUV-ATOFMS. 9-Nitroanthracene, anthraquinone, anthrone, 9,10-dinitroanthracene, 2-, 4-, and 9-nitrophenanthrene, 1-nitropyrene, 1,3-, 1,6-, and 1,8-dinitropyrene, 7-nitrobenzo[a]anthracene, and benzo[a]anthracene-7,12-dione are identified by GC/MS analysis of the reaction products of PAHs and their derivatives coated on the inner bottom surface of the conical flasks with NO₃ radicals. Other oxygenated products are tentatively assigned. 1-Nitropyrene is the only mono-nitrated product detected in the reaction of surface-bound pyrene with gas-phase NO₃ radicals. This phenomenon is different from what has been observed in previous studies of the gas-phase pyrene nitration, showing that 2-nitropyrene is the sole nitration product. The experimental results may reveal the discrepancies between the heterogeneous and homogeneous nitrations of pyrene.